Successful Surgical Repair of Upper Eyelid Lacerations: A Case Series in Five Buffaloes - M Goriya, Yarmiben; Sangwan, Vandana; Gupta, Nikita; Kumar, Ashwani (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The present study compiles five clinical cases of buffaloes presented with upper eyelid lacerations (laterally located) resulting from trauma. The aim was to assess their clinical presentation, surgical repair, and healing outcomes. The duration between trauma and presentation ranged from 1 to 25 days, with the causes mostly attributed to trauma from other buffalo, iron rod or unknown sources. In one buffalo, the laceration was accompanied with prolapse of the lacrimal gland. The lacerations were surgically repaired under sedation and auriculo-palpebral nerve block. Muscles and subcutaneous tissue were sutured in all cases (as per the availability), using absorbable polyglactin 910 and the skin with non-absorbable nylon. The prolapsed lacrimal gland was successfully repositioned prior to closure. The postoperative care included systemic antibiotics, anti-inflammatory medications and topical antibiotic eye ointments. Out of 5 buffaloes, 4 could be followed and all buffaloes had uneventful healing. The study highlights the occurrence of upper lateral eyelid lacerations with or without lacrimal gland prolapse in buffaloes and effectiveness of surgical intervention in restoring eyelid integrity and ocular function, even if presented late.